Need and importance of health protection training in Nepal (Nepal Journal of Epidemiology, 2015)
By investing in health protection, the health of the nation can be safeguarded from future threats of uncontrolled infectious disease epidemics and disasters. DOI: http://dx.doi.org/10.3126/nje.v5i1.12373